Existential-Humanistic Counseling Approach to Improve Self Management in Students - Fatma Sri Kumala Dewi; Yarmis Syukur (Indonesian Institute for Counseling, Education and Theraphy, 2020)
This article discusses students' self-management in managing and managing themselves related to time and the achievement of self-goals using a humanistic existential counseling approach. The study was conducted at one of the High Schools in the City of Padang. Which is done on one student. By using data collection techniques with interviews and observations. The results of this study are that the student knows what he wants and sets out what he will do, already knows clearly what goals he will achieve, understands the goals to be achieved by making plans to achieve what he wants